2006
DOI: 10.1308/003588406x95129
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Total Hip Replacement on the Employment Status of Patients Under the Age of 60 Years

Abstract: Our study demonstrates that total hip replacement is effective in keeping patients under the age of 60 years employed. It is also effective in allowing those already off work due to hip pain to return to work, although there is a much greater delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
76
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 9 publications
8
76
0
2
Order By: Relevance
“…They concluded if patient were off work due to hip pain then total hip replacement would facilitate a return to work. 26 In our group, none of the patients that were unemployed before the operation returned to work. However, Mobasheri et al 26 also reported a reduced rate of re-employment in patients who had been unemployed for more than 1 year before operation.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…They concluded if patient were off work due to hip pain then total hip replacement would facilitate a return to work. 26 In our group, none of the patients that were unemployed before the operation returned to work. However, Mobasheri et al 26 also reported a reduced rate of re-employment in patients who had been unemployed for more than 1 year before operation.…”
Section: Discussionmentioning
confidence: 58%
“…26 In our group, none of the patients that were unemployed before the operation returned to work. However, Mobasheri et al 26 also reported a reduced rate of re-employment in patients who had been unemployed for more than 1 year before operation. The mean period of unemployment in our group before operation was 35 months (range, 21-58 months).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The World Health Organization estimates that 10% of the world's population, over 60 years of age, with osteoarthritis, 80% of the population has movement restriction and 25% have functional limitations in day-to-day activities. This surgery may also be indicated in other situations, such as femoral fracture, common in the elderly, as well as in the treatment of rheumatoid arthritis and avascular necrosis [3].…”
Section: Introductionmentioning
confidence: 99%
“…Podobne wyniki osiągnęli Mobasheri i wsp. [17]. W niniejszych badaniach stwierdzono, że aktywność zawodową po operacji podjęło 40,2% chorych.…”
unclassified